Abnormal audit delays, earnings quality and firm value in the USA. Issue 1 (1st July 2014) - Asthana, Sharad
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to address three questions: Does the abnormal delay in the audit process signal poor earnings quality? Is this information about earnings quality incremental to that contained in earnings report delay? Does the market use this information about earnings quality in valuing the firm? Design/methodology/approach – Data are obtained from four databases: Compustat, Audit Analytics, Compact-Disclosure and I/B/E/S. Complete data are available for 5, 298 firms for 22, 492 firm-years. The paper uses a two-stage model. In the first stage, a detailed model using determinants from extant research tries to explain the audit delay. In the second stage, the unexplained delay from the first stage is used in the association tests with earnings quality. Findings – The paper presents evidence that abnormal delays in the audit process are inversely associated with earnings quality. When the market values a dollar of reported earnings, it appears to discount the valuation by the extent of abnormal audit delay. Originality/value – The current paper contributes to existing research in several ways. First, it establishes a comprehensive model to explain audit delays and provides a tool to measure abnormal audit delays. Second, it provides evidence of inverse association between abnormal audit delay and seven proxies of earnings quality. Finally, the paper shows that abnormal audit delay creates skepticism among investors about earnings quality and they value the disclosed earnings after discounting for such delay.